2003
DOI: 10.1074/jbc.m210908200
|View full text |Cite
|
Sign up to set email alerts
|

Studies with Novel Pdr5p Substrates Demonstrate a Strong Size Dependence for Xenobiotic Efflux

Abstract: The yeast (Saccharomyces cerevisiae) multidrug transporter Pdr5p effluxes a broad range of substrates that are variable in structure and mode of action. Previous work suggested that molecular size and ionization could be important parameters. In this study, we compared the relative sensitivity of isogenic PDR5 and pdr5 strains toward putative substrates that are similar in chemical structure. Three series were used: imidazolecontaining compounds, trialkyltin chlorides, and tetraalkyltin compounds. We demonstra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
78
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 82 publications
(86 citation statements)
references
References 13 publications
8
78
0
Order By: Relevance
“…Doxorubicin is a known substrate of many ABC transporters (Eytan 2005) and deletion of PDR5 leads to hypersensitivity to doxorubicin and many other drugs (Rogers et al 2001;Golin et al 2003). Transport activities for doxorubicin were determined by analytically detecting the fluorescence of the drug in acid soluble supernatants extracted from cells and separated by HPLC ( Figure 2A).…”
Section: Resultsmentioning
confidence: 99%
“…Doxorubicin is a known substrate of many ABC transporters (Eytan 2005) and deletion of PDR5 leads to hypersensitivity to doxorubicin and many other drugs (Rogers et al 2001;Golin et al 2003). Transport activities for doxorubicin were determined by analytically detecting the fluorescence of the drug in acid soluble supernatants extracted from cells and separated by HPLC ( Figure 2A).…”
Section: Resultsmentioning
confidence: 99%
“…The expression of ⌬Cdr1p led to decreased resistance to nystatin, while resistance to miconazole was retained. Recently, by using a variety of novel sub- (14) have reported that this ABC drug transporter from S. cerevisiae has at least three drugbinding sites and suggested that some substrates might even interact at more than one site. Taken together, our results suggest that Cdr1p harbors different drug-binding sites, which recognize structurally dissimilar drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression leads to hyperresistance for all known substrates (13)(14)(15). This efflux pump has a basic structure found in full-length members of this superfamily.…”
mentioning
confidence: 99%